2021
DOI: 10.30811/jpl.v19i1.1956
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: As well known, nonlinear vibration isolation models may offer potential effectiveness for isolating low frequency vibrations. Therefore, this paper will introduce a nonlinear vibration isolation model, featuring asymmetrical and quasi-zero stiffness characteristics. Firstly, the physical model of the nonlinear vibration oscillation is shown, including a semicircular cam-roller and wedge-roller mechanism, in which cylinder adding auxiliary tank is worked as an elastic element. Secondly, its dynamic stiffness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Indeed, the system response is where its inherent properties and possible anomalies are most clearly manifested [36]. Various studies have demonstrated that by isolating and focusing solely on the vibrational response, it is possible to gain a clearer understanding of the dynamic characteristics of the system [37][38][39]. Thus, based on the existing literature and the nature of the data in this work, it is justifiable and methodologically applicable to continue our analysis focusing exclusively on the vibrational responses with the TLCD attached.…”
Section: Presentation and Discussion Of The Main Resultsmentioning
confidence: 99%
“…Indeed, the system response is where its inherent properties and possible anomalies are most clearly manifested [36]. Various studies have demonstrated that by isolating and focusing solely on the vibrational response, it is possible to gain a clearer understanding of the dynamic characteristics of the system [37][38][39]. Thus, based on the existing literature and the nature of the data in this work, it is justifiable and methodologically applicable to continue our analysis focusing exclusively on the vibrational responses with the TLCD attached.…”
Section: Presentation and Discussion Of The Main Resultsmentioning
confidence: 99%